Konfrontation, Kooperation oder Kooptation.: Staat und Anti-Atom-Bewegung im Endlagersuchprozess - Brunnengräber, Achim; Syrovatka, Felix (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2016)
The establishment of a Commission for the Disposal of High-Level Radioactive Waste by the state puts the anti-nuclear movement into a new situation. In the past, the relationship between the movement and the institutions of the state was mainly characterized by confrontation. But the establishment of a Repository Search Committee changed the situation and raised the question of cooperation. Using the hegemony theory, the article analyses the developments and conflicts between the movement and the state in the case of the search process for a nuclear waste repository. Thereby the article mainly focuses on dynamics inside the anti-nuclear movement and the relationship between the different fraction of the movement and the state.